Transfusions of packed red blood cells in the pathology of newborn - Trojanowska, Paulina; Trojanowska, Alina; Tywanek, Ewa; Wronecki, Jakub; Zwolak, Agnieszka; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2019)
Sick newborns are at present the largest group of patients receiving blood products. Therefore packed red blood cells transfusion is one of the most common procedures performed in Intensive Care Units. However, in order to avoid unnecessary risk, and thus reduce the rate of adverse invents after transfusion, which are particularly common in this group of patients, there is a need to develop proper standards of administration.The aim of this study is to review the current scientific literature on transfusion of packed blood cells in different medical situations in neonates.